Tindak Pidana Penyerobatan Tanah Dalam Perspektif Hukum Pidana - Muhammad Ridwan Lubis (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2021)
The title of this Journal is "The Crime of Land Grabbing in a Criminal Law Perspective". The research problems studied in this thesis are how to regulate the crime of land grabbing, how is law enforcement against the crime of land grabbing. The research method used in this research is to use normative juridical research sourced from library research using secondary data which consist of primary legal materials, secondary legal materials and tertiary legal materials.The result of the research shows that the regulation of thecrime of land grabbingis regulated in a number of provisions concerning the crime of land grabbing which is regulated in some provisions of the legislation, including Law Number 51 Prp. 1960 states that the use of land without a permit with the right or legal power is prohibited and punishable by criminal penalties (Article 2 and Article 6) and it is regulated in the Criminal Code in several articles, namely Article 167, Article 242, Article 263, Article 264, Article 266, Article 274, and Article 385 of the Criminal Code.. Law enforcement against the crime of land grabbing is subject to Article 385 of the Criminal Code which is the only article directly related to the land grabbing and is categorized as a criminal offense. Particularly in Article 385 paragraph (1) of the Criminal Code which reads: "whoever with the intention of illegally benefiting himself or another person, sells, exchanges or burdens with credietverbandsomething right to Indonesian land, a building, construction, planting or seeding, even though it is known that it is someone else who owns or shares rights over it. Keywords : Crime, Land Grabbing, Criminal Law.